2017
DOI: 10.2174/1874210601711010312
|View full text |Cite
|
Sign up to set email alerts
|

Insight into Oral Biofilm: Primary, Secondary and Residual Caries and Phyto-Challenged Solutions

Abstract: Abstract:Introduction:

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
55
0
6

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 76 publications
(61 citation statements)
references
References 136 publications
0
55
0
6
Order By: Relevance
“…In addition, opportunistic pathogens Fusobacterium or Leptotrichia, whose abundance we found to be elevated in the Active RAS cohort, have been described as part of the normal oral microbiota [29,30]. Fusobacterium nucleatum has been previously connected to incidence of dental caries and periodontitis [31,32]. Furthermore, F. nucleatum can spread to the intestinal tract and is tightly associated with colorectal carcinoma development [33].…”
Section: Discussionmentioning
confidence: 76%
“…In addition, opportunistic pathogens Fusobacterium or Leptotrichia, whose abundance we found to be elevated in the Active RAS cohort, have been described as part of the normal oral microbiota [29,30]. Fusobacterium nucleatum has been previously connected to incidence of dental caries and periodontitis [31,32]. Furthermore, F. nucleatum can spread to the intestinal tract and is tightly associated with colorectal carcinoma development [33].…”
Section: Discussionmentioning
confidence: 76%
“…The S-layer present at the outermost cell surface of some Lactobacillus species is responsible for cell surface hydrophobicity 95 . Vadillo-Rodríguez et al, studied on the cell surface hydrophobicity of two species of Lactobacillus, they concluded that in a low ionic strength suspension, both Lactobacillus strains show higher initial deposition rates to hydrophobic glass than to hydrophilic glass, whereas in a high ionic strength suspension no clear influence of cell surface hydrophobicity on adhesion is observed 65,96,97,121 .…”
Section: Cell Surface Hydrophobicity: Attachment Ofmentioning
confidence: 99%
“…So far, various EPS-producing Lactobacillus species have been identified such as L. casei, L. acidophilus, L. brevis, L. curvatus, L. delbrueckii subsp. bulgaricus, L. helveticus, L. rhamnosus, L. plantarum, and L. johnsonii 65,97,98 .…”
Section: Exopolysaccharide Produced By Lactobacillusmentioning
confidence: 99%
See 1 more Smart Citation
“…Both caries and periodontal disease can lead to tooth loss. Thus, dental biofilm plays a fundamental role in the pathogenic process of oral diseases (Chenicheri, R, Ramachandran, Thomas, & Wood, ; Wolff, Frese, Maier‐Kraus, Krueger, & Wolff, ). This way, the prevention and treatment of caries and periodontal disease benefit from antimicrobial strategies (Nazar Majeed, Philip, Alabsi, Pushparajan, & Swaminathan, ; Serrano, Escribano, Roldán, Martín, & Herrera, ; Wang et al, ).…”
Section: Introductionmentioning
confidence: 99%